Scientific Research in Midwifery and Health Adolescent Reproduction - Sembiring, Tamaulina Br.; Kembaren, Novalina Br. (PT FORMOSA CENDEKIA GLOBAL, 2024)
The research method applied is qualitative with a phenomenological approach. Thematic analysis technique was used to analyze the data obtained. The results showed that adolescents' knowledge about reproductive health is still limited and diverse. The majority of adolescents get information from peers and social media, while sources of information from family and school are still lacking. Factors that contribute to risky behavior include lack of comprehensive sexual education, peer pressure, and limited access to reproductive health services. The conclusion of this study highlights the importance of improving comprehensive reproductive health education at school and within the family. In addition, easier and more youth-friendly access to reproductive health services is needed. These effects are expected to reduce risky behaviors and improve overall adolescent reproductive health.